Temperature and magnetic field dependence of the critical current density for a mass-produced Nb3Al multifilamentary strand fabricated by a jelly-roll method [for ITER]. - Takahashi, Y. (IEEE Transactions on applied superconductivity)
JAERI has been developing jelly-roll processed multifilamentary Nb3Al-Cu strands for the toroidal field (TF) coils of fusion tokamak machines since 1986, in cooperation with Sumitomo Electric Industries. One ton of mass-produced strands were successfully manufactured for the 13 T-46 kA Nb3 Al insert which will be tested in the ITER Central Solenoid model coil. The critical current of the Nb3Al strand developed for the ITER project was measured in temperatures from 4.2 to 15 K and in applied magnetic fields up to 16 T. An empirical equation for the critical current density Was obtained by using these data and the pinning force scaling method. The obtained equation is useful in evaluating the performance of the full-size conductor and in establishing the optimum design criteria for the conductor in fusion machines. In this work, we did not take into account the influence of mechanical strain on the strand. IC measurement of the strands under mechanical strain will be carried out and an expression for JC with the strain will be completed in the next phase.